Performans Induk Sapi Silangan Simmental – Peranakan Ongole dan Induk Sapi Peranakan Ongole dengan Pakan Hijauan dan Konsentrat (Performance of Simmental – Ongole Crossbred Cow and Ongole Crossbred Cow Fed with Forage and Concentrate Feed) - Eny Endrawati; Endang Baliarti; Subur Priyono Sasmito Budi (Buletin Peternakan, 2010)
The purposed of the study was to identify performances of Simmental – Ongole Crossbred (SIMPO) cow and Ongole Crossbred (PO) cow fed with forage and concentrate feed. This experiment was carried out at Laboratory ofMeat, Draught, and Companion Animals, Faculty of Animal Science, Universitas Gadjah Mada, Yogyakarta on May 16th to July 24th 2009. Six SIMPO cows with initial body weight of 352±47 kg and ten PO cows with initial body weightof 295±60 kg aged 3-4 years was used in the experiments. They were fed with elephant grasses and concentrate feds (60:40/DM basis) as much as 3% of body weight (DM basis). Data collected were dry matter, organic matter, crudeprotein and total digestible nutrients intakes, dry matter, organic matter, and crude protein digestibilities, body condition score and estrus cycles. Experimental design used was Completely Randomized Design (CRD). The dataoptained showed that feed intake of dry matter, organic matter, crude protein, and TDN on SIMPO were higher (P<0.01) than PO (13.99±2.64 kg/head/day vs 10.95±1.03 kg/head/day; 11.74±2.21 kg/head/day vs 9.17±0.87kg/head/day; 1.63±0.29 kg/head/day vs 1.28±0.11 kg/head/day; 7.53±1.41 kg/head/day vs 6.17±0.60 kg/head/day respectively), whereas there were no significant differences on the nutrient intake expressed in metabolic body weight(0.16±0.02 kgMBW vs 0.14±0.02 kgMBW; 0.13±0.02 kgMBW vs 0.12±0.02 kgMBW; 0.018±0.002 kgMBW vs 0.02±0.002 kgMBW; 0.09±0.01 kgMBW vs 0.08±0.01 kgMBW) respectively. There were no difference both on drymatter, organic matter, crude protein digestibility (70.83±3.26% vs 65.36±2.19%; 72.38±3.08% vs 67.10±2.15%; 79.48±2.29% vs 75.79±2.17%), and so were in the case of BCS, and estrus cycles in SIMPO and PO cow. It is concluded that based on the metabolic body weight and feed digestibility, between SIMPO and PO cows were similar.(Key words: Performance, Cow, Simmental – Ongole Crossbred cow, Ongole Crossbred cow, Forage, Concentrate)